Analisa Keterkaitan Permainan dan Strategi Pembelajaran Terhadap Pelaksanaan Kurikulum Merdeka Belajar PAUD - Yossi Srianita; Dwiyani Anggraeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Play is the most important activity which gave children time to learn about their community beside them. In play children can grow all of their growth. Learning Strategy is all teacher do with use and combination learning methods to achieve the learning goals. Learning strategy which are; direct instruction, human instruction, group instruction, deductive and inductive instruction. This research use kualitative methode which descriptive combine with the library research. The subject research are early childhood teachers at Cikarang Baru. The result research get from library research, observation and interview with subjects. The result of this reseach are: all early childhood teacher already knew about the definition dan function of playing activity, but teacher have some problems which their have difficult to choose the right kind of play that can be use for the goal learning program, and theacher must be solve of the parents wants are children must be can reading, writing and counting when their enter the primary grade